Microsponges – a novel carrier for resiquimod - Ab. Hadi, Hazrina; Zaiter, Ahmad (2017)
Microsponge is a polymeric drug delivery system composed of spherical particles ranged in micron size and loaded with active pharmaceutical ingredient. Microsponges have maximum residency on the skin and slow release rate. Resiquimod is a candidate drug to be entrapped in microsponge drug delivery system. Formulation of resiquimod loaded microsponges was done using oil in water emulsion solvent evaporation method. The method had two phases, organic and aqueous phase. Three types of solvent were used in organic phase along with four volumes. Dichloromethane (DCM), chloroform and ethyl acetate (EA) were the solvent in organic phase with the volumes were used 1, 2.5, 5, 10 mL. Different formulations of microsponges using different volumes of solvents were prepared. From twelve microsponges formulations, three were chosen to be incorporated in aqueous gel. Microsponges prepared by 2.5 mL of DCM, 1 mL of chloroform or 5 mL of EA were selected and coded as F1, F2 and F3. Microsponges were evaluated for % entrapment efficiency (EE), average particle size (PS), span value (SV), and % production yield (PY). For determination of % EE and quantification of resiquimod in skin and percutaneous penetration samples, two reversed phase high performance liquid chromatographic methods were developed and validated. Differential scanning calorimetry (DSC) was used to evaluate the physical nature of resiquimod in microsponges. For both unincorporated and incorporated microsponges in gels, field emission scanning electron microscopy (FESEM) and Fourier transform infrared spectroscopy (FTIR) were used. The release and drug disposition from microsponges gels were evaluated by Franz diffusion cells using human skin. The highest % EE was 47.05 ± 1.88 and observed at 1 mL of chloroform. In contrast, the lowest % EE 12.7 ± 3.9 resulted from using 10 mL of EA. The range of PS was from 38 ± 9.96 to 2.44 ± 1.14. The SV for all of formulations was less than 2, which was an indication of monodispersity of PS. The percent of PY ranged from 79.02 ± 0.97 to 28.84 ± 3.35 for 1 mL DCM and 10 mL of EA. The FESEM results showed that there were no crystals on the surface of any microsponges as well as integrity and sphericity were preserved when incorporated in gel. DSC results of microsponges suggested amorphous nature of entrapped resiquimod in microsponges. Whereas, FTIR spectrums of loaded microsponges against non-loaded suggested no chemical interaction between resiquimod and ethylcellulose polymer. While FTIR results of lyophilized loaded and non-loaded microsponges gels suggested no chemical interaction between microsponges and gel excipients. F1 formulation had 7 times lower flux 2.97 ± 0.25 µg/cm2/hr compared to resiquimod control gel 20.55 ± 8.86 µg/cm2/hr while F2 and F3 had no flux. Results of quantified resiquimod in SC were 0.56 ± 0.26, 0.55 ± 0.30, 0.51 ± 0.30 and 1.04 ± 0.17 µg/cm2 for F1, F2, F3 and control gel respectively. On the other hand, quantified resiquimod in epidermis plus dermis were 0.88 ± 0.30, 0.36 ± 0.12, 0.16 ± 0.05 and 0.17 ± 0.05 µg/cm2 for F1, F2, F3 and control gel respectively. Resiquimod loaded microsponges in gel resulted localization of resiquimod in skin layers and minimal flux.